Teacher's Strategy to Realize Students' Collaboration Ability in Class VI in Limited Face-to-Face Learning in Elementary Schools - Rezki, Nur Ariani Sri (Program Magister Teknologi Pendidikan Universitas Jambi, 2017)
This research aims to describe the results of the analysis of teachers' strategies for realizing students' collaborative abilities in class VI in limited face-to-face learning in elementary schools. At the time of research, learning implementation was currently carried out using a limited face-to-face learning system. This research was conducted at State Elementary School 111/I Muara Bulian. This type of research is qualitative research. The techniques used are observation, interviews and documentation. This research describes all forms of actions and phenomena carried out by the subjects studied. By making direct and indirect observations in the field. The results of this research indicate that the sixth grade teacher has implemented limited face-to-face learning activities using strategies to realize students' cooperation abilities. The form of strategy used is an interactive learning strategy through cultivating indicators of cooperative ability, namely: 1) collaborative, implementing small group learning methods. 2) contribute, encourage and give students opportunities to express their opinions in discussions. 3) communication, being an example and training students so that their self-confidence emerges. 4) caring, instilling that the task is an obligation even if the student is unable to attend. 5) responsive, giving questions that guide students to respond to other people's opinions, and 6) participation, providing understanding through assessment.